Restoration of mangrove forests: resilience of pedogenetic processes and soil quality - Jimenez, Laís Coutinho Zayas (2019)
Mangroves are coastal ecosystems that provide many ecosystem services, for example: (i) carbon sequestration; (ii) mitigation of greenhouse gas emissions; (iii) retention and immobilization of contaminants; (iv) nursery for several marine species; so it is necessary to develop mangrove protection and recovery initiatives, which are among the most impacted and degraded ecosystems in the world. In addition, many ecosystem services are related to pedogenetic soil processes, however, few studies have carried out this approach. Therefore, this study aimed to analyze two mangrove recovery initiatives in different soil contexts, aiming at identifying the restoration of pedogenetic processes and soil quality. Therefore, two mangroves with reforestation areas were analyzed in two compartments of the Brazilian coast: a) one in the state of Ceará (CE) located in the northeast region marked by a source material rich in quartz and semiarid climate; b) another located in the state of Rio de Janeiro (RJ), in the Southeast region, which presents material rich in iron and a humid tropical climate. In both sites, it was possible to observe the reestablishment of pedogenetic processes such as paludization, gleization and sulfidization, which are related to ecosystem services such as carbon sequestration and retention and immobilization of contaminants. Our study also identified the soil quality improvement using the Soil Management Assessment Framework (SMAF) tool, it is emphasized that this approach has never been used in studies involving mangroves. In fact, mangrove revegetation initiatives were able to increase soil quality of parameters such as: bulk density, carbon content, phosphorus content and pH, and the increase in soil quality positively affected the restoration of ecosystem functions such as sequestering carbon. In addition, the SMAF tool proved to be a useful tool for studies of soil quality, however, adjustments should be considered, as well as the number of variables inserted. In general we also identify that the reestablishment of pedogenetic processes may occur in a short period of time and that this approach is fundamental to infer about the capacity of impacted mangroves to develop their ecosystem functions.